Robotic-assisted radical prostatectomy learning curve for experienced laparoscopic surgeons: does it really exist? - Tobias-Machado,Marcos (2016)
ABSTRACT Background Robotic-assisted radical prostatectomy (RALP) is a minimally invasive procedure that could have a reduced learning curve for unfamiliar laparoscopic surgeon. However, there are no consensuses regarding the impact of previous laparoscopic experience on the learning curve of RALP. We report on a functional and perioperative outcome comparison between our initial 60 cases of RALP and last 60 cases of laparoscopic radical prostatectomy (LRP), performed by three experienced laparoscopic surgeons with a 200+LRP cases experience. Materials and Methods Between January 2010 and September 2013, a total of 60 consecutive patients who have undergone RALP were prospectively evaluated and compared to the last 60 cases of LRP. Data included demographic data, operative duration, blood loss, transfusion rate, positive surgical margins, hospital stay, complications and potency and continence rates. Results The mean operative time and blood loss were higher in RALP (236 versus 153 minutes, p<0.001 and 245.6 versus 202ml p<0.001). Potency rates at 6 months were higher in RALP (70% versus 50% p=0.02). Positive surgical margins were also higher in RALP (31.6% versus 12.5%, p=0.01). Continence rates at 6 months were similar (93.3% versus 89.3% p=0.43). Patient’s age, complication rates and length of hospital stay were similar for both groups. Conclusions Experienced laparoscopic surgeons (ELS) present a learning curve for RALP only demonstrated by longer operative time and clinically insignificant blood loss. Our initial results demonstrated similar perioperative and functional outcomes for both approaches. ELS were able to achieve satisfactory oncological and functional results during the learning curve period for RALP.